Atomic physics : precise measurements and ultracold matter - Inguscio, M.; Fallani, L. (Leonardo) (Oxford University Press, 2013)
This book illustrates the history of Atomic Physics and shows how its most recent advances allow the possibility of performing precise measurements and achieving an accurate control on the atomic state. Written in an introductory style, this book is addressed to advanced undergraduate and graduate students, as well as to more experienced researchers who need to remain up-to-date with the most recent advances. The book focuses on experimental investigations, illustrating milestoneexperiments and key experimental techniques, and discusses the results and the challenges of contemporary research.